PELATIHAN PEMBUATAN UNIT PENGOLAH AIR SUMUR GALI YANG MENGANDUNG BESI (Fe) DAN MANGAN (Mn) MENGGUNAKAN METODE KOMBINASI KLORINASI-FILTRASI DAN ZEOLIT DI PERUMAHAN MILALA DESA NAMO BINTANG KECAMATAN PANCUR BATU - Haesti Sembiring; Nelson Tanjung (Indonesian Collaboration Journal of Community Services, 2022)
Many dug wells are found in areas that have not been reached by PDAM. Because dug wells do not require large costs to manufacture. However, dug well water often contains minerals that exceed the maximum permissible levels. Dug wells are one of the facilities for providing clean water to the community in the Milala Housing Center, Blok E Hamlet VI, Namo Bintang Village, Pancur Batu District. The visible condition of the dug well water: the water is very yellow in color. The results of the examination of iron and manganese levels in the water carried out in a 2020 study by the author turned out that the levels of both substances were above the threshold for drinking water and clean water requirements. The iron content is more than 4 mg/l and the manganese content is in the range of 2.60 - 3.02 mg/l. Based on the results of research that has been carried out by the author, it is known that the method of treating dug well water which is suitable for reducing iron and manganese levels in this area is to use the chlorination-filtration method and zeolite, where the ability of this method can reduce 98% iron content and manganese content. 90%